Exportaciones de harina de pescado del Perú, 2018-2022 - Ruiz García Calderón, Bianka Brunell (2024)
The purpose of this study is to determine the exports of fishmeal from Peru during the period 2018-2022. Therefore, data on various indicators was collected, such as the FOB value, price and volume, as well as the main destination markets and associated export companies. This study is non-experimental quantitative with a descriptive approach, its technique is documentary analysis and a content analysis instrument, to achieve this objective it was necessary to select information from national and international pages. The results of this study reveal significant effects on Peruvian fishmeal exports, which grew by 4.06% between 2018 and 2021. Seasonality shows peaks in June and minimums in November, with China being the main destination market followed by Japan and Germany. The Balassa index highlights the Peruvian advantage in the export of fishmeal to China, with fluctuations due to the pandemic. In Peru, companies such as Tecnologica deAlimentas S.A. and Pesquera Diamante S.A. They faced reductions due to the pandemic and the El Niño phenomenon, indicating greater competition over time. These results confirm the importance of optimizing the marketing of anchovy meal and maximizing the economic and social benefits for producing countries to improve the marketing of anchovy meal and benefit producing countries by generating income for development and employment. This study provides valuable information on the constant increase in fishmeal exports during the period from 2018 to 2022, with China leading as the main destination due to its strong advantage in importing Peruvian fishmeal, followed by Japan and Germany. Furthermore, it was observed that the main companies in this industry show a moderate degree of concentration, without having dominant control.